Completion of Maize Stripe Virus Genome Sequence and Analysis of Diverse Isolates - Bolus, Stephen; Braithwaite, Kathryn S.; Grinstead, Samuel C.; Fuentes-Bueno, Irazema; Beiriger, Robert; Falk, Bryce W.; Mollov, Dimitre (Frontiers in Microbiology, 2021)
Maize stripe virus is a pathogen of corn and sorghum in subtropical and tropical regions worldwide. We used high-throughput sequencing to obtain the complete nucleotide sequence for the reference genome of maize stripe virus and to sequence the genomes of ten additional isolates collected from the United States or Papua New Guinea. Genetically, maize stripe virus is most closely related to rice stripe virus. We completed and characterized the RNA1 sequence for maize stripe virus, which revealed a large open reading frame encoding a putative protein with ovarian tumor-like cysteine protease, endonuclease, and RNA-dependent RNA polymerase domains. Phylogenetic and amino acid identity analyses among geographically diverse isolates revealed evidence for reassortment in RNA3 that was correlated with the absence of RNA5. This study yielded a complete and updated genetic description of the tenuivirus maize stripe virus and provided insight into potential mechanisms underpinning its diversity.